The Gangster Films - Hughes, Ed (The Ozu Collection, 2013)
The latest volume in the BFI's collection of the works of Japanese master Yasujirô Ozu focuses on his crime films. Ozu honed his craft in the early 1930s, a time when young Japanese directors were experimenting with cinematic conventions. In these rare silent works, Ozu mixes Hollywood-infused dynamism with elements of his later unique, poetic style. Each film is presented with a newly commissioned score by Ed Hughes. [www.moviemail.com]